2021
DOI: 10.3389/fmicb.2021.695447
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and Intercropping With Potato–Onion Enhanced the Growth and Yield Advantages of Tomato by Regulating the Soil Properties, Nutrient Uptake, and Soil Microbial Community

Abstract: The application of biochar stimulates the activities of microorganisms that affect soil quality and plant growth. However, studies on the impacts of biochar mainly focus on a monoculture, its effects on interspecific interactions are rarely reported. Here, we investigated the impacts of biochar on tomato/potato–onion intercropped (TO) in a pot experiment. Tomato monoculture (T) and TO were treated with no, 0.3, 0.6, and 1.2% biochar concentrations in a pot experiment. Microbial communities from tomato rhizosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 82 publications
1
15
1
Order By: Relevance
“…In general, biochar treatment increased plant height by 66.6%, leaf number by 45.1%, and nodule number by 35.9% over control treatment (Table 1). Several researchers have reported that biochar application improves plant growth, development, and yield in different plants [29,30,32,34,39]. Similarly, Saxena et al [27] found that root length, shoot length, and root biomass were positively impacted by biochar treatment, also seen by Zheng et al [64], where biochar treatment increased the plant biomass of Chinese cabbage.…”
Section: Impact Of Biochar and Amf On Fenugreek Plant Growth Parametersmentioning
confidence: 86%
See 2 more Smart Citations
“…In general, biochar treatment increased plant height by 66.6%, leaf number by 45.1%, and nodule number by 35.9% over control treatment (Table 1). Several researchers have reported that biochar application improves plant growth, development, and yield in different plants [29,30,32,34,39]. Similarly, Saxena et al [27] found that root length, shoot length, and root biomass were positively impacted by biochar treatment, also seen by Zheng et al [64], where biochar treatment increased the plant biomass of Chinese cabbage.…”
Section: Impact Of Biochar and Amf On Fenugreek Plant Growth Parametersmentioning
confidence: 86%
“…Trupiano et al [34] found that morphological traits were enhanced in biochar applications (Figure 5). All reports discussed the beneficial effect that biochar is believed to help boost soil fertility by increasing soil acidity [27,30,32,34]. AMF are beneficial symbiotic fungi improving plant growth, development, and plant nutrient uptake in various crops.…”
Section: Impact Of Biochar and Amf On Fenugreek Plant Growth Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The LNM treatment significantly decreased the abundance of some pathogenic biomarkers, such as Kribbella (ASV_181600) and Burkholderiaceae (ASV_161133, ASV_107576, ASV_467163, ASV_311539, ASV_175182), which were enriched in the excessive nitrogen treatment (HN) with low yield. Therefore, inorganic–organic mixed fertilizer application may alleviate the adverse effects of excessive nitrogen input on wheat yield and promote wheat growth from the bacterial perspective (He et al, 2021). However, a balance between the application of inorganic and organic fertilizer application in agroecosystems may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Non-metric multidimensional scaling (NMDS) ( Jiao et al, 2017 ; Khashi u Rahman et al, 2021 ) was applied to simplify samples or OUTs in high-dimensional to low-dimensional space for location using the “metaMDS” function based on the Bray–Curtis distance ( He et al, 2021 ). Linear discriminant analysis (LDA) effect size (LEfSe) was run to determine the significantly enriched clades (LDA scores ≥ 2 and p < 0.05).…”
Section: Methodsmentioning
confidence: 99%